PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARING (PBL) UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V PADA TEMA 9 BENDA-BENDA DISEKITAR KITA DI SDN 1 DORANG - Diva Ramadhan Niawati Sunarsih; Erik Aditia Ismaya; Imaniar Purbasari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
The thematic learning process in class V shows that the learning process is not oriented towards critical thinking skills. This is shown when the teacher rarely gives students the opportunity to ask questions during the learning process, and evaluation questions and evaluation questions given at the end of learning or sub-themes have not been directed at developing students' critical thinking skills. The purpose of this research is to find out how to increase the teaching skills of teachers, increase students' critical thinking skills and the learning activities of fifth grade students at SDN 1 Dorang by applying the Problem Based Learning model. This class action research was carried out in class V SDN 1 Dorang with 14 students and teachers as research subjects which were carried out in two cycles, namely cycle one and cycle consisting of 4 stages (1) planning, (2) action (3) observation (4) reflection . The results of this study showed an increase in students' critical thinking skills in cycle I obtaining an average score of 73.81 with low qualifications with classical completeness of 78,57% in cycle II obtaining an average score of 89.65 good qualification with classical completeness of 85,71%